FACILITATING COMPLEX THINKING IN EDUCATIONAL PSYCHOLOGY(The Perspectives of Kelvin Seifert and Rosemary Sutton) (Indonesian Journal of Education (INJOE), 2025)
Teaching involves a variety of instructional strategies, where decisions and actions are designed to facilitate learning. The choice of strategy depends in part on the forms of thinking aimed at the student-whether the goal is for students to think critically, for example, or to think creatively, or to solve problems